Finding Medical Care for Colorectal Cancer Symptoms: Experiences Among Those Facing Financial Barriers. (February 2015) - Thomson, Maria D.; Siminoff, Laura A.
Financial barriers can substantially delay medical care seeking. Using patient narratives provided by 252 colorectal cancer patients, we explored the experience of financial barriers to care seeking. Of the 252 patients interviewed, 84 identified financial barriers as a significant hurdle to obtaining health care for their colorectal cancer symptoms. Using verbatim transcripts of the narratives collected from patients between 2008 and 2010, three themes were identified: insurance status as a barrier (discussed by n = 84; 100% of subsample), finding medical care (discussed by n = 30; 36% of subsample) and, insurance companies as barriers (discussed by n = 7; 8% of subsample). Our analysis revealed that insurance status is more nuanced than the categories insured/uninsured and differentially affects how patients attempt to secure health care. While barriers to medical care for the uninsured have been well documented, the experiences of those who are underinsured are less well understood. To improve outcomes in these patients it is critical to understand how financial barriers to medical care are manifested. Even with anticipated changes of the Affordable Care Act, it remains important to understand how perceived financial barriers may be influencing patient behaviors, particularly those who have limited health care options due to insufficient health insurance coverage.